A free-standing, self-healing multi-stimuli responsive gel showing cryogenic magnetic cooling. Issue 38 (23rd September 2020) - Adhikary, Amit; Das, Krishna Sundar; Saha, Sayan; Roy, Manasi; Mondal, Raju
Abstract : A novel Fe(iii )-based gel was synthesized where reported gel would be the first reported metallogel showing magnetocaloric effect. The metallogel also revealed outstanding colourimetric NH3 sensing with unique gel-to-gel transformation. Abstract : A novel Fe(iii )-based gel was synthesized via the self-assembly of Fe(iii ) and pyridine 2, 6 dicarboxylic acid. The synthesized gel has remarkable mechanical strength as well as self-sustainability. The metallogel also has thixotropic as well as self-healing properties. The metallogel shows amazing colourimetric NH3 sensing with unique gel-to-gel transformation. Magnetic studies on the as-synthesized gel reveal significant cryogenic magnetic cooling behavior. Last but not least, to the best of our knowledge, this would be the first case where MCE is investigated for any reported metallogel.